EFL Student Teachers’ Speaking Anxiety: the Case in One English Teacher Education Program - Mukhlash Abrar; F Failasofah; Nunung Fajaryani; M Masbirorotni (IJEE (Indonesian Journal of English Education), 2016)
ABSTRACT This present study examined student teachers’ Foreign Language Speaking Anxiety (FLSA) associated with gender and proficiency differences. The participants of the study were 72 second-year EFL student teachers at the English teacher education program of one public university in Jambi, Indonesia. A close-ended questionnaire developed from Syakur (1987) and Horwitz et al, (1986) was administered to the participants to explore their FLSA. The results indicated that EFL student teachers are highly anxious when speaking English. Furthermore, the findings revealed that there is no statistical difference between male and female student teachers on FLSA. On the contrary, proficiency does affect EFL learners’ anxiety wherein more proficient students seem to be less nervous to speak. ABSTRAK Penelitian ini membahas kecemasan berbicara bahasa asing (FLSA) siswa yang dihubungkan dengan perbedaan jenis kelamin dan kecakapan berbahasa Inggris. Jumlah peserta dalam penelitian ini sebanyak 72 mahasiswa tahun kedua pada program studi pendidikan bahasa Inggris di salah satu universitas negeri di Jambi. Kuesioner tertutup diberikan kepada peserta penelitian untuk mengetahui FLSA mereka. Hasil penelitian mengindikasikan bahwa siswa pembelajar bahasa asing (EFL) sangat cemas ketika berbicara bahasa Inggris. Selain itu, hasil juga menunjukkan bahwa tidak ada perbedaan statistik yang signifikan pada FLSA antara siswa laki-laki dan perempuan. Sebaliknya, tingkat kecakapan sangat mempengaruhi kecemasan siswa EFL dimana siswa yang mempunyai kecakapan dalam bahasa Inggris terlihat tidak terlalu cemas untuk berbicara. How to Cite: Abrar, M. Failasofah. Fajaryani, N. Masbirorotni. (2016). EFL Student Teachers’ Speaking Anxiety: the Case in One English Teacher Education Program. IJEE (Indonesian Journal of English Education), 3(1), 60-75. doi:10.15408/ijee.v3i1.3619 Permalink/DOI: http://dx.doi.org/10.15408/ijee.v3i1.3619